Influence of pouring temperature and alloy additions on the quality of a semisolid material dragged during the continuous-casting strip processing of al-si a413 - Filho, Antonio de Pádua Lima [UNESP]; Ferreira, Lucas Veronez Goulart [UNESP]; Neto, Pedro Barbosa de Oliveira [UNESP]; de Oliveira, Cássio Basile [UNESP]; Arantes, Carlos Henrique de Oliveira [UNESP]; de Castro, Tales Paschoalino [UNESP]; Borodiak, Miguel; Quadro, Alexandre Leão (Trans Tech Publications, 2019)
Al–Si A413 treated and untreated alloys were cast and poured at approximately 720 ºC, 700 ºC, and 680 ºC in a cooling slope to obtain the semisolid material feeding the ceramic nozzle (150 cm 3 ) at the lower roll (single-roll melt-dragged processing)—this drags the metallic slurry via the chill/columnar layers at a rate of 0.2 m/s, forming a molten-metal strip with a thickness of 2 mm and width 45 mm, approximately. The untreated alloy poured at 720 ºC formed coarse structures of α-Al dendrites, as well as a coarse eutectic of Al–Si and microshrinking on the surface of the casting strip facing the atmosphere. The Al–Si 413 alloy poured at 680 ºC and treated with Al5Ti1B (0.1%) led to microstructural refinement, resulting in α-Al globular structures, the absence of microporosities on the surface facing the atmosphere, and a finer and more homogeneous distribution of the eutectic grains with smaller Si particles. The AlTiB master alloys are not used as a grain refiner in Al–Si alloys because of Si poisoning. This subject is discussed in this paper. The addition of the inoculant and 0.2% of the Al–Si eutectic morphology modifying agent (Al–10%Sr) refined both the α-Al and eutectic phases more efficiently in the cast strip poured at 700 ºC and 680 ºC. This suggests that the inoculant did not interfere with the action of the modifying agent. As a result, molten metal strips of higher mechanical strengths and ductilities were obtained.
Keywords: Al-Si A413; Al-Si modification; Al-Sr; Al5Ti1B; Cast metallic strips; Grain refining